Use of Electrical Resistivity Tomography for Joint Geophysical and Geotechnical Landslide Characterization: A Case Study - Kherrouba Hassiba; Lamara Mohammed; Benzaid Riad (Selected Scientific Papers: Journal of Civil Engineering, 2023)
Slope movement processes include complex soil and rock failure mechanisms. Their study benefits from a multidisciplinary approach based on a wide range of information including geological and geomorphological mapping, and geotechnical and geophysical investigations. This research paper focuses on the characterization of the Tamentout landslide that occurs in the southeast of Jijel province. The study area belongs to the Tellian domain in which the geological outcrops are dominated by Senonian formations, composed of marl deposits overlain by Numidian flysch of Aquitano-Burdigalian age, with a sloping topography ranging from 20° to 30°. The geophysical approach consists of processing the available geophysical data of resistivity, obtained by the Electrical Resistivity Tomography (ERT). This study aims to characterize the internal structure, and the changes in water saturation within the unstable mass and locate the depth of slip surface associated with this landslide. Through this work, we combined geological and geotechnical investigations with electrical resistivity tomography (ERT). This combination gave a more detailed image of the substrate geology and structure of the landslide zone. The 2D resistivity results show that the basement consists of two main formations. The first one is a highly conductive formation with a resistivity range between 2 and 25 Ωm, a depth of 0-8 m, and is interpreted as a saturated marl-clay overlaying. The second, a hard and compact formation with a resistivity range between 50 and 200 Ωm and a depth range of 8 to 40 m, was interpreted as a substrate of tellian marls. The presence of boulders of Numidian sandstone within the two formations is materialized by a very high resistivity value ranging from 500 to 1000 Ωm. The slip surface was located on the layer with low resistivity (2-25 Ωm). The precise determination of the depth of the shear zone is of vital use in implementing mitigation measures and carrying out the stabilization work of this unstable zone. Through this work, we will highlight the advantage of the combination of available results of the geological, geotechnical investigations and electrical resistivity tomography (ERT) carried out in the study area.